Expressive Language of Poetry as a Means of Artistic Communication - Takhmina Kamiljonovna Akramova (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Poetic language has long functioned as a distinctive form of artistic and emotional communication. Specific Background: Despite a detailed understanding of poetic techniques, there remains limited clarity about how these elements function as mechanisms of communication and artistic evolution. Knowledge Gap: Existing studies often overlook the specific communicative structures and socio-aesthetic functions that enable poetry to mediate individual and collective experiences. Aims: This study investigates the expressive language of poetry as a communicative tool, analyzing how metaphor, symbolism, sound, rhythm, and ambiguity shape artistic discourse. Results: Through interdisciplinary methods combining literary theory, linguistics, and cultural criticism, the study demonstrates that poetry communicates multilayered meanings—emotional, intellectual, and political—beyond what practical language can convey. Novelty: By positioning poetic language not merely as aesthetic ornamentation but as a structured communicative system, this research offers a reconceptualization of poetry’s function within art and society. Implications: The findings affirm poetry's role in cultural transmission and identity formation, reinforcing its relevance as a dynamic medium for articulating complex human realities and fostering societal cohesion. Highlight : Metaphor and Symbolism: Poetry uses metaphor and symbolism to express deep emotional and intellectual ideas, creating shared understanding. Sound and Rhythm: The auditory elements of poetry enhance emotional impact and mirror human thought patterns. Ambiguity: Poetic language thrives on open interpretation, allowing diverse personal and cultural meanings. Keywords : Metaphor, Symbolism, Poetic Language, Communication, Rhythm